Assessment of Relationship between Fyn-related Kinase Gene Polymorphisms and Overweight/Obesity in Korean Population - Jung, Mi-Young; Kim, Bum-Shik; Kim, Youn-Jung; Koh, In-Song; Chung, Joo-Ho (The Korean journal of physiology & pharmacology, 2008)
The fyn-related kinase (FRK) belongs to the tyrosine kinase family of protein kinases. Recent studies have shown that Frk affects pancreatic beta cell number during embryogenesis and promotes beta cell cytotoxic signals in response to streptozotocin. To investigate the genetic association between FRK polymorphisms and the risk of obesity in Korean population, single nucleotide polymorphisms (SNPs) in the FRK gene region were selected and analyzed. The body mass index (BMI) was calculated, and biochemical data (systolic blood pressure, diastolic blood pressure, hemoglobin A1C, triglyceride, total cholesterol, high density lipoprotein, and low density lipoprotein) of blood sample from each subject were also measured. One hundred fifty five healthy control and 204 overweight/obesity subjects were recruited. Genotype frequencies of six SNPs [rs6568920 (+8391G>A), rs3756772 (+56780A>G), rs3798234 (+75687C>T), rs9384970 (+68506G>A), rs1933739 (+72978G>A), and rs9400883 (+75809A>G)] in the FRK gene were determined by Affymetrix Targeted Genotyping Chip data. According to the classification of Korean Society for the Study of Obesity, control (BMI 18 to < 23) and overweight/obesity (BMI$≥$23) subjects were recruited. For the analysis of genetic data, EM algorithm, SNPStats, Haploview, HapAnalyzer, SNPAnalyzer, and Helixtree programs were used. Multiple logistic regression analysis (codominant, dominant, and recessive models) was performed. Age and gender as covariates were adjusted. For biochemical data, Student's t test was used. The mean value of BMI in the control and overweigh/obesity groups was 21.1${±}$1.2 (mean${±}$SD) and 25.6${±}$2.0, respectively. All biochemical data of the overweight/obesity group were statistically significance, compared with the control group. Among six SNPs, two linkage disequilibrium (LD) blocks were discovered. One block consisted of rs1933739 and rs9400883, and the other comprised rs3756772 and rs3798234. One SNP (rs9384970, +68506G>A) showed an association with overweight/obesity in the codominant model (p=0.03). Interestingly, the AA genotype distribution in the overweight/obesity group (n=7, 3.5%) was higher than those in the control group (n=1, 0.6%), which is not found in either Japanese or Chinese subjects. Therefore, the AA genotype of rs9384970 may be a risk factor for development of obesity in Korean population. The results suggest that FRK may be associated with overweight/obesity in Korean population.